PENGARUH RASIO CAPITAL ADEQUACY, LOAN TO DEPOSIT, NET INTEREST MARGIN TERHADAP PERTUMBUHANLABA (STUDI KASUS PADA BANK UMUM KONVENSIONALYANG TERDAFTAR DI BURSA EFEK INDONESIA) - Bambang Suryadi; Lis Djuniar (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2017)
This study is how Influence Ratio Capital Adequacy Ratio, Loan to Deposit Ratio, Net Interest Margin Against Profit Growth at Conventional Commercial Banks Listed on Indonesia Stock Exchange. the purpose of this study is to analyze the Influence of Capital Adequacy Ratio Ratio, Loan to Deposit Ratio, Net Interest Margin on Profit Growth at Conventional Commercial Banks Listed on Indonesia Stock Exchange. The type of research used is associative research. The research population is conventional commercial bank in Indonesia. The research variables are Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), and Profit Growth. The data used is secondary data. Data collection methods are quantitative. Partial test results show that NIM has a significant effect on Profit Growth, While CAR and LDR have no significant effect to Profit Growth.